(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
This article explores the challenges of achieving sustainability in food supply. The article explores the cause of food waste in areas and its environmental negative effects and develops recommendations.